(untitled) (Journal of Misan Researches, 2024)
The study discusses the importance of French diplomatic archive documents as an important source for the historical writing of the Arabian Gulf region in modern times (19-20 AD). The Diplomatic Archives Center "La Courneuve" in Paris keeps this type of diplomatic documents, such as those related to the Arab Gulf region in the form of reports and telegrams issued by French consulates in the Arab Gulf, its archives included many events witnessed by the region during this period, such as the internal situation of the Arab Gulf region, and the Franco-British rivalry over commercial interests and spheres of influence in the Arab Gulf, which caused crises between them in the region, such as the crisis in the hoisting of French flags on Omani ships and the expansion of the arms trade. These records provide us with important details about the seasons of pilgrimage of Muslims from European colonies, and other documents reveal information about the rulers and cities of the United Arab Emirates during this time. and for clarification, this study has been supplemented with examples from the Arabian Gulf archives kept at this center.